Resin composition, its manufacturing method, and use
The resin composition addresses high dielectric loss and permittivity issues by enhancing compatibility and mechanical properties, enabling high-performance circuit boards for 5G communication products.
Patent Information
- Application Number
- JP2024538761
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-31
- Filing Date
- 2022-12-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-29
AI Technical Summary
Conventional circuit board base materials face challenges with high dielectric loss, permittivity, low peel strength, and insufficient mechanical properties, limiting their application in 5G communication electronic products.
A resin composition comprising hydrocarbon resin, bismaleimide resin, polyphenylene ether resin, inorganic filler, and flame retardant, produced through prepolymerization of allylbenzoxazine and hydrocarbon resin, improves compatibility and mechanical properties, reducing dielectric loss and constant while enhancing peel strength.
The resin composition achieves lower dielectric loss and constant, higher peel strength, and improved mechanical properties, making it suitable for high-performance circuit boards.
Smart Images

Figure 2024545907000001 
Figure 2024545907000002 
Figure 2024545907000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of resin materials, in particular to a resin composition and its manufacturing method and use. [Background technology]
[0002] With the rapid development of the electronics industry, electronic products are developed in the direction of miniaturization, high functionality and high safety, which requires electronic components to have higher signal propagation speed and transmission efficiency, and places higher requirements on the substrate of the circuit board, which is required to have high heat resistance, peel resistance and excellent mechanical properties on the one hand, and low water absorption, dielectric constant and dielectric loss value on the other hand.
[0003] Conventional circuit board substrates are generally manufactured using diamine-modified or allyl-modified bismaleimide resins, but such bismaleimide resin materials have defects such as high curing temperature, high water absorption, high dielectric constant and loss value, which limits their application in the field of 5G communication electronic products. Therefore, how to further reduce the dielectric loss and dielectric constant has become one of the important research directions for the modification of bismaleimide resin materials.
[0004] Hydrocarbon resins have excellent dielectric properties and are widely used in the field of 5G communication electronic products. However, due to their flexibility and non-polar carbon chain structure, the cured products have insufficient rigidity, low strength, low heat resistance, low glass transition temperature, low peel strength and other problems, which limit their use.
[0005] Research has provided a resin composition that contains as its components a hydrocarbon resin, a bismaleimide resin, a polyphenylene ether resin, an initiator, an inorganic filler, a flame retardant and a solvent, and that has a high glass transition temperature and excellent heat resistance. However, the hydrocarbon resin in the composition has low polarity, and therefore has low compatibility with the highly polar bismaleimide resin, resulting in a low peel strength of the material, and making it impossible to achieve both peel strength and dielectric properties. Summary of the Invention [Problem to be solved by the invention]
[0006] Based on this, the present invention provides a resin composition having low dielectric loss and dielectric constant as well as good peel strength, and a method for producing the same and use thereof. [Means for solving the problem]
[0007] The specific technical measures are as follows:
[0008] The first aspect of the present invention comprises, as raw material components, in parts by weight: 10-30 parts of hydrocarbon resin prepolymer, 50 to 100 parts of bismaleimide resin, 30 to 80 parts of cyanate ester resin, 5 to 30 parts of functional resin, 10 to 60 parts of inorganic filler, and Contains 10 to 20 parts of flame retardant, The hydrocarbon resin prepolymer provides a resin composition prepared by prepolymerizing allylbenzoxazine and a hydrocarbon resin.
[0009] In one embodiment, the arylbenzoxazine is one or more selected from the group consisting of the following structures: [ka] [ka] and [ka] R 1 ~R 3 are each independently -CH 2 -, -C(CH 3 ) 2 -, -S(=O) 2 - and -O-.
[0010] In one embodiment, the hydrocarbon resin is one or more selected from the group consisting of polybutadiene, epoxidized polybutadiene, butadiene-styrene copolymer, and butadiene-acrylic acid copolymer.
[0011] In one embodiment, the mass ratio of the allylbenzoxazine to the hydrocarbon resin is 100:(10-50).
[0012] In one embodiment, the method for preparing the hydrocarbon resin prepolymer includes the steps of mixing the allylbenzoxazine and a hydrocarbon resin, and heating the mixture at 100 to 130° C. for 1 to 3 hours to prepare the hydrocarbon resin prepolymer.
[0013] In one embodiment, the bismaleimide resin is selected from organic compounds having two or more maleimide structures in their molecular structure.
[0014] In one embodiment, the maleimide structure is one or more selected from the group consisting of an N-phenylmaleimide group, an N-(2-methylphenyl)maleimide group, an N-(4-methylphenyl)maleimide group, an N-(2,6-dimethylphenyl)maleimide group, a bis(4-maleimidophenyl)methane group, a 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane group, a bis(3,5-dimethyl-4-maleimidophenyl)methane group, a bis(3-ethyl-5-methyl-4-maleimidophenyl)methane group, a bis(3,5-diethyl-4-maleimidophenyl)methane group, a polyphenylmethane bismaleimide group, and a biphenyl structure-containing maleimide group.
[0015] In one embodiment, the cyanate ester resin is one or more selected from the group consisting of bisphenol A type cyanate ester resin, novolac type cyanate ester resin, bisphenol F type cyanate ester resin, multifunctional type cyanate ester resin, bisphenol M type cyanate ester resin, bisphenol E type cyanate ester resin and dicyclopentadiene bisphenol type cyanate ester resin.
[0016] In one embodiment, the functional resin is one or more selected from the group consisting of epoxy resin and polyphenylene ether.
[0017] In one embodiment, the inorganic filler is one or more selected from the group consisting of zirconium vanadate, zirconium tungstate, hafnium tungstate, crystallized glass, eucryptite, silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc powder, alumina, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay, and kaolin.
[0018] In one embodiment, the flame retardant is selected from halogen-free flame retardants.
[0019] In one embodiment, the resin composition further comprises, by weight, 1 to 5 parts of an auxiliary.
[0020] In one embodiment, the coagent is one or more selected from the group consisting of accelerators, coupling agents and toughening agents.
[0021] A second aspect of the present invention provides a method for producing the above-mentioned resin composition, comprising the step of mixing the raw material components to produce the resin composition.
[0022] A third aspect of the present invention provides the use of the above resin composition in the manufacture of a laminate. Effect of the Invention
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a method for producing a hydrocarbon resin prepolymer using allylbenzoxazine and a hydrocarbon resin, producing a resin composition with a bismaleimide resin and other components in a reasonable blending ratio, and prepolymerizing the resin composition using allylbenzoxazine to improve the compatibility between the hydrocarbon resin and the bismaleimide resin and further improve the peel strength and dielectric properties of the material. By using the resin composition as a base material for a circuit board, the dielectric loss and dielectric constant of the material can be effectively reduced and the material has a high peel strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] In order to facilitate understanding of the present invention, the present invention will now be described more fully with reference to the following examples. Preferred examples of the present invention are set forth below. However, the present invention may be embodied in many different forms and is not limited to the examples set forth herein. On the contrary, the purpose of providing these examples is to provide a more complete and thorough understanding of the present disclosure.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The terms used herein in describing the present invention are for the purpose of describing specific examples only and are not intended to be limiting of the present invention.
[0027] As used herein, the scope of the term "and / or," "or / and," and "and / or" includes any one item of two or more associated listed items, and further includes any and all combinations of the associated listed items, including combinations of any two associated listed items, any more associated listed items, or all associated listed items.
[0028] In the present invention, the terms "first embodiment", "second embodiment", "third embodiment", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or quantity, nor should they be understood as implying the importance or quantity of the technical features indicated. It should also be understood that "first", "second", "third", etc., serve the purpose of a non-exhaustive enumeration description only and do not constitute closed-type limitations on the quantities.
[0029] In the present invention, technical features described in an open format include both closed technical solutions consisting of the listed features and open technical solutions including the listed features.
[0030] In the present invention, unless otherwise specified, a numerical range is considered to be continuous within the numerical range, and includes the minimum and maximum values of the range, and each value between the minimum and maximum values. In addition, when a range indicates an integer, each integer between the minimum and maximum values of the range is included. In addition, when there are multiple ranges describing a feature or characteristic, they may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges subsumed therein.
[0031] Unless otherwise specified, the temperature parameter in the present invention may be a constant temperature treatment or may be a treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range of the equipment control.
[0032] The present invention comprises, as raw material components in parts by mass: 10-30 parts of hydrocarbon resin prepolymer, 50 to 100 parts of bismaleimide resin, 30 to 80 parts of cyanate ester resin, 5 to 30 parts of functional resin, 10 to 60 parts of inorganic filler, and Contains 10 to 20 parts of flame retardant, The hydrocarbon resin prepolymer provides a resin composition prepared by prepolymerizing allylbenzoxazine and a hydrocarbon resin.
[0033] The present invention involves producing a hydrocarbon resin prepolymer using allylbenzoxazine and a hydrocarbon resin, improving the compatibility of the hydrocarbon resin with other highly polar resins, such as bismaleimide resins, by means of prepolymerization, and further using a resin composition produced with other components in a reasonable blending ratio as a base material for a circuit board, thereby effectively reducing the dielectric loss and dielectric constant of the material and providing it with high peel strength.
[0034] In the present invention, the hydrocarbon resin has excellent dielectric properties, and its soft segment significantly improves the brittleness of the bismaleimide resin, and the bismaleimide resin can improve its glass transition temperature and high-temperature elastic modulus. By carrying out prepolymerization using allylbenzoxazine, the compatibility between the two is improved, which is advantageous in improving the heat resistance and mechanical properties when the produced resin composition is used as a base material for a circuit board.
[0035] In one example, the arylbenzoxazine is one or more selected from the group consisting of the following structures: [ka] [ka] and [ka] R 1 ~R 3 are each independently -CH 2-, -C(CH 3 ) 2 -, -S(=O) 2 - and -O-. 1 ~R 3 are each independently -CH 2 -, -C(CH 3 ) 2 -, -S(=O) 2 -or -O-.
[0036] In one example, the hydrocarbon resin is one or more selected from the group consisting of polybutadiene, epoxidized polybutadiene, butadiene-styrene copolymer, and butadiene-acrylic acid copolymer.
[0037] In one example, the mass ratio of allylbenzoxazine to hydrocarbon resin is 100:(10 to 50). Further, the mass ratio of allylbenzoxazine to hydrocarbon resin includes, but is not limited to, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, and 100:50.
[0038] In one example, the method for producing a hydrocarbon resin prepolymer includes the steps of mixing allyl benzoxazine and a hydrocarbon resin and heating for 1 to 3 hours under conditions of 100 to 130° C. to produce a hydrocarbon resin prepolymer. Furthermore, the heating temperature after mixing allyl benzoxazine and a hydrocarbon resin includes, but is not limited to, 100° C., 105° C., 110° C., 115° C., 120° C., 125° C., and 130° C., and the heating time includes, but is not limited to, 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours.
[0039] In the present invention, the bismaleimide resin is not particularly limited, and may be an organic compound containing two or more maleimide structures in its molecular structure. Furthermore, the maleimide structure is one or more selected from the group consisting of N-phenylmaleimide group, N-(2-methylphenyl)maleimide group, N-(4-methylphenyl)maleimide group, N-(2,6-dimethylphenyl)maleimide group, bis(4-maleimidophenyl)methane group, 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane group, bis(3,5-dimethyl-4-maleimidophenyl)methane group, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane group, bis(3,5-diethyl-4-maleimidophenyl)methane group, polyphenylmethane bismaleimide group, and biphenyl structure-containing maleimide group.
[0040] In one example, the cyanate ester resin is one or more selected from the group consisting of bisphenol A type cyanate ester resin, novolac type cyanate ester resin, bisphenol F type cyanate ester resin, multifunctional type cyanate ester resin, bisphenol M type cyanate ester resin, bisphenol E type cyanate ester resin, and dicyclopentadiene bisphenol type cyanate ester resin.
[0041] In one example, the functional resin is one or more selected from the group consisting of epoxy resins and polyphenylene ethers.
[0042] In one example, the inorganic filler is one or more selected from the group consisting of zirconium vanadate, zirconium tungstate, hafnium tungstate, crystallized glass, eucryptite, silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc powder, alumina, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay, and kaolin.
[0043] In one example, the flame retardant is a non-halogen flame retardant.Furthermore, the flame retardant includes, but is not limited to, a phosphorus-containing flame retardant and a silicon-containing flame retardant.Note that the phosphorus-containing flame retardant may be a phosphorus-containing epoxy resin, a phosphorus-containing phenolic resin, a phosphazene compound, a phosphoric acid ester compound, etc., and the silicon-containing flame retardant may be a silicone polymer, etc.
[0044] In one example, the resin composition further comprises, by mass, 1 to 5 parts of an auxiliary.
[0045] In one example, the coagent is one or more selected from the group consisting of a cure accelerator, a coupling agent, and a toughening agent.
[0046] The curing accelerator, coupling agent and reinforcing agent may be selected from conventional curing accelerators, coupling agents and reinforcing agents in this field, the curing accelerator may be selected from, but is not limited to, imidazole-based curing agents, organometallic salt-based curing agents and peroxide-based curing agents, and the reinforcing agent may be selected from, but is not limited to, rubber, silicone resin and phenoxy resin.
[0047] The present invention further provides a method for producing the above-mentioned resin composition, comprising the step of mixing raw material components to produce a resin composition.
[0048] In addition, when producing the resin composition, an organic solvent that is advantageous for dissolving and mixing the raw material components in the production process may be added, and the organic solvent may be selected from organic solvents commonly used in this field. Furthermore, the organic solvent may be one kind of organic solvent or a mixed solvent of two or more kinds of organic solvents.
[0049] The present invention further provides the use of the resin composition in the manufacture of a laminate.
[0050] In the present invention, a hydrocarbon resin prepolymer is first prepared using allylbenzoxazine and a hydrocarbon resin, and then a resin composition is prepared with a bismaleimide resin and other components in a reasonable mixing ratio, and the laminate prepared from the resin composition has lower dielectric loss and dielectric constant, as well as good peel strength. The laminate prepared from the resin composition also has excellent heat resistance and mechanical properties. EXAMPLES
[0051] The present invention will be described in more detail with reference to specific examples below. Unless otherwise specified, all raw materials, reagents, etc. used in the following examples are commercially available.
[0052] The raw materials used in the examples and comparative examples of the present invention are as follows.
[0053] The bismaleimide resin is BMI-01 manufactured by Honghu Soumachang, and its structure is as follows: [ka]
[0054] The cyanate ester resin is BA-3000S manufactured by Lonza Group. The phosphazene compound is SPB100 manufactured by Otsuka Chemical Co., Ltd. The epoxy resin is XD1000 manufactured by Nippon Kayaku Co., Ltd. Polyphenylene ether is SA9000 manufactured by Saudi Basic Industries Corporation. The polybutadiene is B-1000 manufactured by Nippon Soda Co., Ltd. The hardening accelerator is DCP. The silica is SO-C2 manufactured by Admatechs.
[0055] 1. Preparation of Hydrocarbon Resin Prepolymer 1 100 parts of allylbenzoxazine and 20 parts of polybutadiene were placed in a three-neck flask, and an appropriate amount of a mixed solvent of toluene and butanone was added, followed by heating to 120°C in an oil bath and stirring continuously for 2.5 hours to obtain hydrocarbon resin prepolymer 1. Allylbenzoxazine was purchased from Chengdu Keyi Company, Ltd., and its model number is CB6900.
[0056] 2. Preparation of Hydrocarbon Resin Prepolymer 2 100 parts of allylbenzoxazine and 70 parts of polybutadiene were placed in a three-neck flask, and an appropriate amount of a mixed solvent of toluene and butanone was added, and then the mixture was heated to 120°C in an oil bath and stirred continuously for 2.5 hours to obtain a hydrocarbon resin prepolymer 2. Allylbenzoxazine was purchased from Kolon Co., Ltd., and its model number was KZH-5031MP70.
[0057] 3. Production of Hydrocarbon Resin Prepolymer 3 100 parts of allylbenzoxazine and 20 parts of butadiene-styrene copolymer were placed in a three-neck flask, and an appropriate amount of organic solvent was added, followed by heating to 120°C in an oil bath and stirring continuously for 2.5 hours to obtain hydrocarbon resin prepolymer 3. Allylbenzoxazine was purchased from Chengdu Keyi Company, Ltd., and its model number is CB6900.
[0058] 4. Prepreg manufacturing The emulsion liquid (i.e., resin composition) of each Example and Comparative Example was prepared using the raw material components and compounding ratios shown in Table 1 below. Then, 2116 glass cloth was immersed in each emulsion liquid and baked in an oven at 160℃ for 3 minutes to obtain a prepreg with an emulsion content of 55%.
[0059] [Table 1]
[0060] 5. Manufacturing of laminates Ten prepregs prepared in each Example and Comparative Example were laminated to obtain a laminate corresponding to each Example and Comparative Example. The laminate was covered on both the top and bottom surfaces with a sheet of electrolytic copper foil having a thickness of 18 μm, and placed in a vacuum press with programmable temperature and pressure controls, and then heated to 30 kgf / cm under vacuum. 2 After heat-press curing at a pressure of 180°C for 1 hour + 220°C for 2 hours + 240°C for 2 hours, a copper foil-clad laminate with a thickness of 1.0 mm was obtained.
[0061] 6. Performance Test Performance tests were carried out on the copper foil-clad laminates produced in Examples 1 to 4 and Comparative Examples 1 to 4. The results are shown in Table 2.
[0062] [Table 2]
[0063] The more ★'s, the higher the compatibility. The more ☆'s, the higher the impact resistance.
[0064] The test method is as follows. (1) Regarding compatibility, the resin was left in a room temperature environment and allowed to stand, and the presence or absence of precipitation of any substance was visually observed. (2) Glass transition temperature (Tg) / storage modulus was tested in accordance with IPC-TM650 2.4.25D. (3) Peel strength was tested in accordance with IPC-TM-650 2.4.8. (4) The heat resistance of the tin plating was tested in accordance with IPC-TM650 2.4.6. (5)PCT was tested in accordance with IPC-TM650 2.6.23. (6) Flexural modulus was tested in accordance with IPC-TM650 2.4.4. (7) Flame retardancy level was tested in accordance with IPC-TM650 2.3.10. (8) The drop weight impact test was conducted using a drop weight impact tester. (9) Dielectric properties were tested in accordance with IPC-TM650 2.5.5.2.
[0065] The technical features of the above-mentioned embodiments may be combined in any combination. For the sake of brevity, all possible combinations of the technical features of the above-mentioned embodiments are not described, but all such combinations should be considered to fall within the scope of the present specification.
[0066] The above describes some aspects of the present invention with reference to specific examples, but should not be understood as limiting the scope of the patent of the present invention. It should be noted that those skilled in the art can make various modifications and improvements to the present invention without departing from the spirit of the present invention, and these modifications and improvements also fall within the scope of the present invention. Therefore, the scope of protection of the patent of the present invention is determined by the appended claims.
Claims
1. In parts by mass, as raw material components: 10 to 30 parts of a hydrocarbon resin prepolymer, 50 to 100 parts of bismaleimide resin, 30 to 80 parts of cyanate ester resin, 5 to 30 parts of functional resin, 10 to 60 parts of inorganic filler, and Contains 10 to 20 parts of a flame retardant, A resin composition, characterized in that the hydrocarbon resin prepolymer is produced by prepolymerizing allylbenzoxazine and a hydrocarbon resin.
2. The allylbenzoxazine is one or more selected from the group consisting of the following structures: 【Chemistry 1】 【Chemistry 2】 and 【Chemistry 3】 R 1 ~R 3 are each independently -CH 2 -, -C(CH 3 ) 2 -, -S(=O) 2 2. The resin composition according to claim 1, wherein the radical is one or more radicals selected from the group consisting of - and -O-.
3. 2. The resin composition according to claim 1, wherein the hydrocarbon resin is one or more selected from the group consisting of polybutadiene, epoxidized polybutadiene, butadiene-styrene copolymer, and butadiene-acrylic acid copolymer.
4. 2. The resin composition according to claim 1, wherein a mass ratio of the allylbenzoxazine to the hydrocarbon resin is 100:(10 to 50).
5. The method for producing the hydrocarbon resin prepolymer comprises: The resin composition according to claim 1, further comprising a step of mixing the allylbenzoxazine and a hydrocarbon resin and heating the mixture at 100 to 130° C. for 1 to 3 hours to produce the hydrocarbon resin prepolymer.
6. 2. The resin composition according to claim 1, wherein the bismaleimide resin is selected from organic compounds having two or more maleimide structures in their molecular structure.
7. The resin composition according to claim 6, characterized in that the maleimide structure is one or more selected from the group consisting of an N-phenylmaleimide group, an N-(2-methylphenyl)maleimide group, an N-(4-methylphenyl)maleimide group, an N-(2,6-dimethylphenyl)maleimide group, a bis(4-maleimidophenyl)methane group, a 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane group, a bis(3,5-dimethyl-4-maleimidophenyl)methane group, a bis(3-ethyl-5-methyl-4-maleimidophenyl)methane group, a bis(3,5-diethyl-4-maleimidophenyl)methane group, a polyphenylmethane bismaleimide group, and a biphenyl structure-containing maleimide group.
8. The resin composition according to any one of claims 1 to 7, characterized in that the cyanate ester resin is one or more selected from the group consisting of bisphenol A type cyanate ester resins, novolac type cyanate ester resins, bisphenol F type cyanate ester resins, multifunctional cyanate ester resins, bisphenol M type cyanate ester resins, bisphenol E type cyanate ester resins, and dicyclopentadiene bisphenol type cyanate ester resins.
9. The resin composition according to any one of claims 1 to 7, wherein the functional resin is one or more selected from the group consisting of epoxy resins and polyphenylene ethers.
10. The resin composition according to any one of claims 1 to 7, characterized in that the inorganic filler is one or more selected from the group consisting of zirconium vanadate, zirconium tungstate, hafnium tungstate, crystallized glass, eucryptite, silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc powder, alumina, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay, and kaolin.
11. The resin composition according to any one of claims 1 to 7, characterized in that the flame retardant is selected from halogen-free flame retardants.
12. The resin composition according to any one of claims 1 to 7, further comprising, by weight, 1 to 5 parts of an auxiliary agent.
13. The resin composition according to claim 12, wherein the auxiliary is one or more selected from the group consisting of a curing accelerator, a coupling agent, and a reinforcing agent.
14. A method for producing the resin composition according to any one of claims 1 to 13, A method for producing the resin composition, comprising the step of mixing the raw material components.
15. Use of the resin composition according to any one of claims 1 to 13 in the manufacture of laminates.
Citation Information
Patent Citations
Low-dielectric high-heat-resistance benzoxazine resin containing hydrocarbon chain segment and polyphenyl ether chain segment and preparation method of low-dielectric high-heat-resistance benzoxazine resin
CN113637133A
Low-dielectric-loss copolymer composition and prepreg and laminated board made of low-dielectric-loss copolymer composition
CN113801435A
Cured body, b-stage film, and multilayer printed wiring board
JP2021123687A
Low dielectric halogen-free resin composition and circuit board using the same
US20140349090A1
Resin composition and article made therefrom
US20210009759A1
